Short-Term Value Creation in LVMH’s Acquisition of Tiffany & Co. : A Case Study with Financial and Corporate Governance Perspectives - Nurminen, Stina (My University, 2025)
Mergers and acquisitions have played a significant role in driving the growth of the modern luxury market. They have also enabled Bernard Arnault, the CEO and Chairman of LVMH, to build a French conglomerate comprising 75 prestigious brands over the years. Through a successful growth strategy, LVMH has become the world leader in the luxury goods sector, becoming the first European company to reach a market value of USD 500 billion in 2023. This study focuses on examining LVMH’s most significant acquisition, that of the world-renowned jewellery brand Tiffany & Co., which also represents the largest acquisition in the luxury goods sector, with a final price of nearly USD 16 billion. This mixed-methods research integrates an analysis of Tiffany’s share price reactions to assess short-term value creation with an evaluation of how LVMH’s family-owned governance structure influenced the strategic motives and valuation of the acquisition. Market reactions are examined through an event study, in which changes in calculated abnormal returns and cumulative abnormal returns are analysed across the five most significant event dates related to the acquisition. The market-adjusted returns model uses historical price data retrieved from LSEG Workspace (Refinitiv) for both Tiffany shares and the S&P 500 benchmark index. The event study indicates that LVMH’s preliminary acquisition announcement at the end of October 2019 caused the largest positive market reaction, with an abnormal return exceeding 30%. Throughout the acquisition process, the market responded immediately to public announcements, which supports the semistrong form of the Efficient Market Hypothesis. LVMH appears to have benefited from Arnault’s established position and extensive experience in executing major strategic acquisitions. During the COVID-19 pandemic, Arnault was able to capitalise on market conditions and Tiffany’s weakened profitability, ultimately securing a slightly lower purchase price through renegotiations.

Yrityskaupat ja fuusiot ovat olleet merkittävässä roolissa modernin luksusmarkkinan kasvun vauhdittajina. Niiden ansiosta LVMH:n toimitusjohtaja ja hallituksen puheenjohtaja Bernard Arnault on myös vuosien saatossa pystynyt rakentamaan 75 arvostetusta brändistä koostuvan ranskalaisen monialayrityksen. Menestyksekkään kasvustrategian avulla, LVMH on noussut maailman johtavaksi toimijaksi luksustuotteiden alalla ja ensimmäiseksi eurooppalaiseksi yritykseksi, jonka markkina-arvo saavutti 500 miljardia Yhdysvaltain dollaria vuonna 2023. Tämä tutkimus keskittyy tarkastelemaan LVMH:n merkittävintä yritysostoa, maailmankuulun korumerkin Tiffany & Co:n hankintaa, joka on myös suurin yritysosto luksustuotteiden alalla. Kaupan lopullinen hinta oli lähes 16 miljardia Yhdysvaltain dollaria. Tämä monimenetelmäinen tutkimus yhdistää analyysin Tiffanyn osakekurssin reaktioista lyhyen aikavälin arvonluonnin arvioimiseksi ja tarkastelun siitä, kuinka LVMH:n perheomisteinen hallintorakenne vaikutti yrityskaupan strategisiin motiiveihin ja arvostukseen. Markkinareaktioita tarkastellaan tapahtumatutkimuksen avulla, jossa analysoidaan laskettujen epänormaalien tuottojen ja kumulatiivisten epänormaalien tuottojen muutoksia yrityskaupan viiden merkittävimmän tapahtumapäivän aikana. Markkinakorjatun tuoton mallissa käytetään LSEG Workspacesta (Refinitiv) haettua historiallista hintadataa sekä Tiffanyn osakkeista että S&P 500 -vertailuindeksistä. Tapahtumatutkimus osoittaa, että LVMH:n alustava yritysostoilmoitus lokakuun 2019 lopussa aiheutti suurimman positiivisen markkinareaktion, jonka epänormaali tuotto oli yli 30 %. Hankintaprosessin aikana markkinat reagoivat välittömästi julkisiin ilmoituksiin, mikä tukee tehokkaiden markkinoiden hypoteesin keskivahvaa muotoa. LVMH:n voidaan katsoa hyötyneen Arnaultin vakiintuneesta asemasta ja laajasta kokemuksesta merkittävien strategisten yrityskauppojen toteuttamisessa. COVID-19-pandemian aikana Arnault pystyi hyödyntämään markkinatilannetta ja Tiffanyn heikentynyttä kannattavuutta, mikä lopulta johti hieman alhaisemman ostohinnan saavuttamiseen uudelleenneuvottelujen myötä.
Keywords: LVMH, Tiffany, M&A, luxury acquisition, event study, abnormal returns, corporate governance, family ownership, LVMH, Tiffany, yrityskaupat ja fuusiot, luksusalan yrityskauppa, tapahtumatutkimus, epänormaalit tuotot, yrityksen hallintotapa, perheomistus